PCS-13 The Profile and Morphology of Proboscis Monkey’s Blood Cells in South Kalimantan - Irma Padeta; Rini Widayanti; Heri Budi Santoso; Amalia Rezeki; Teguh Budipitojo (Hemera Zoa, 2018)
Twenty percent of primate species is found in Indonesia1. Proboscis monkey (Nasalis larvtaus) or bekantan is one of endemic species in Kalimantan2,3. This primate is belonging to Colobinae subfamily and distributed in Kalimantan (Indonesia), Sabah and Serawak (Malaysia), and Brunei. Proboscis monkey is belonging to endangered species based on International Union for the Conservation of Nature and Natural Resources (IUCN) assessment4. Indonesian Ministry of environment and forestry established Proboscis monkey is belonging to one of twenty five species which has been incrased in population.Blood cells have important role in body regulation such as maintaining body temperature, carriying oxygen, nutrition, hormone and metabolism product to the whole body5. Blood examination is important for body health evaluation6,7, especially in non-human primate where lived in zoo, animal captive or rehabilitiation center6. The aim of this study was to investigate the profile and morphology of female-juvenile proboscis monkey blood cells at rehabilitation center (Sahabat Bekantan Indonesia Foundation) in Banjarmasin, South Kalimantan.